Fibrinogen Bergamo I (Aα16Arg → Cys): Susceptibility Towards Thrombin Following Aminoethylation, Methylation or Carboxamidomethylation of Cysteine Residues - Reber, P; Furlan, M; Beck, E A; Finazzi, G; Buelli, M; Barbui, T (Thrombosis and Haemostasis, 1985)
An abnormal fibrinogen, denoted as “fibrinogen Bergamo I”, has been characterized. Its defect consists in an exchange of arginine by cysteine in position 16 of the Aα-chain, thus corresponding to that found in a number of other fibrinogen variants. The abnormal fibrinopeptide A cannot be split off by thrombin from intact fibrinogen Bergamo I. We describe three different chemical modifications of the cysteine Aαl6, i.e. aminoethylation, methylation and carboxamidomethylation, and their effects on the susceptibility of fibrinogen Bergamo I towards thrombin attack. S-aminoethylation of the Aαl6Cys renders the peptide bond Aαl6–17 cleavable by thrombin. Following methylation or carboxamidomethylation, the Aαl9-arginyl bond becomes accessible for thrombin. The chemically modified extended fibrinopeptide A can be readily separated from the normal fibrinopeptide A by HPLC. The latter two modifications are suitable alternative procedures for detecting the molecular defect Aαl6Arg → Cys of fibrinogen.
Keywords: Dysfibrinogenemia; Fibrinogen Bergamo I